Calidad del servicio en la Cooperativa de Transporte 20 de Febrero del cantón Vinces - Zurita Villasagua, Ruben Eduardo (2021)
The quality of service is something very fundamental in any service activity that is carried out, since depending on this, the satisfaction of customers / users who have the use of said service will be framed, in public transport this quality must be denoted and practiced daily, in the Cooperativa de Transporte 20 de Febrero of the canton Vinces, through the case study carried out, we must frame how satisfactory the service is, the present case study is carried out with the aim of analyzing how the quality of service is by part of these units that make up the Cooperative and that makes this happen, since there are problems such as abbreviated units, lack of biosecurity measures, high passage rates, or any other that directly affect the user and resulting in the service provided is not adequate and the disagreement exists. To carry out this study, we resorted to the use of a study method such as the user survey and interview with the president, which were given in order to collect information, observe and learn about the problems in the quality of the service provided by part of the aforementioned Cooperative, since this will lead us to conclude on how the quality of service provided is considered and if the problems specifically have their beginning from each of the units or in the internal administrative environment of the Cooperative.